Research and verification of key issues in 5G network - Wei LIU; Jiangbo DONG; Yebing REN (Dianxin kexue)
The first edition of 5G techni cal specification has been frozen on June 2018,and the end to end products have also been steadily developing.The 5G network s cale test has been launched,to clear strategy for introducing technology and new technologies.The development of 5G industry in the world was introduced.And then the key issues of 5G were combed from 3 dimensions.Finally,the basic situation of the 5G s cale test was introduced,including the principles and objectives,the overall plan and the test content.